Pengaruh Pemberian Mobilisasi Dini ROM (Range Of Motion) Pasif Ekstremitas terhadap Perubahan Aldrete Score pada Pasca General Anestesi - Marta Tania Gabriel Cing Ching; Dwi Teguh Faizah (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Providing passive ROM to the extremities can help improve blood circulation, improve respiratory function, and support the recovery of consciousness as assessed using the Aldrete Score. The purpose of this study was to determine the effect of providing early passive ROM mobilization of the extremities on changes in the Aldrete score in patients after general anesthesia. This study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 57 respondents. The intervention provided was early passive ROM mobilization. The Aldrete score was measured before and after the intervention. Data analysis used the Wilcoxon signed rank test with a significance level of α = 0.05. The results showed that the average Aldrete score before the intervention was 5.89 and after the intervention increased to 9.26. The results of the statistical test showed a p value = 0.0001 (p <0.05), which means that there is a significant effect of providing early passive ROM mobilization of the extremities on increasing the Aldrete score after general anesthesia. From this study, it can be concluded that there is an effect of providing early passive ROM mobilization of the extremities on increasing the Aldrete score after general anesthesia.